2014
DOI: 10.1681/asn.2013040387
|View full text |Cite
|
Sign up to set email alerts
|

Activated Omentum Slows Progression of CKD

Abstract: Stem cells show promise in the treatment of AKI but do not survive long term after injection. However, organ repair has been achieved by extending and attaching the omentum, a fatty tissue lying above the stomach containing stem cells, to various organs. To examine whether fusing the omentum to a subtotally nephrectomized kidney could slow the progression of CKD, we used two groups of rats: an experimental group undergoing 5/6 nephrectomy only and a control group undergoing 5/6 nephrectomy and complete omentec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In recent years, findings by several groups have supported the notion that mesothelial cells isolated from adult rodents have regenerative potential [ 2 5 ]. Mesothelial cells constitute a simple squamous epithelium that lines the coelomic cavities as parietal mesothelium and surrounds the organs within coelomic cavities as visceral mesothelium.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, findings by several groups have supported the notion that mesothelial cells isolated from adult rodents have regenerative potential [ 2 5 ]. Mesothelial cells constitute a simple squamous epithelium that lines the coelomic cavities as parietal mesothelium and surrounds the organs within coelomic cavities as visceral mesothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our results, Garcia-Gomez et al reported omentum was effective in treatment of kidney injuries, as was alternative source of adult stem cells. In the context of the use of omentum, progression to CKD (Chronic Kidney Disease) could be reduced in this rat model (11). But in this research kidney injuries were large capacity as like 5/6 subtotal nephrectomy.…”
Section: Discussionmentioning
confidence: 77%
“…But, they can live very short time in the tissue, if they are injected into the target.In many studies, the omentum has been used to wrap the injured tissue and has been shown to be useful. According to the results of the research, the progression to the chronic kidney failure has been shown to more slowly in subtotal nephrectomies that are covered by omentum (11). This is a unique contribution in the context of nephron-sparing.…”
mentioning
confidence: 97%
“…Garcia-Gomez et al . [ 27 ] showed that 6 weeks after 5/6 NPX, fusing the polydextran gel particle activated omentum to the remnant kidney resulted in higher creatinine clearance and lower plasma creatinine/urea nitrogen levels. Our results showed that the pedicled omentum packing ESC-loaded GMs on the 5/6 nephrectomized kidney exhibited significantly lower plasma creatinine/urea nitrogen levels at 4 weeks, which was an earlier time frame.…”
Section: Discussionmentioning
confidence: 99%